The Digital Learning Role in Reducing Educational Loss Among Students from Teachers’ Perceptions in Irbid Governorate - Obeidat, Belal Hosain (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to identify the role of digital learning in reducing educational loss among students from teachers’ perceptions in Irbid governorate. Methods: To achieve that, a descriptive approach was used, and a questionnaire consisting of (32) items distributed into four domains: (cognitive loss, skill loss, emotional loss, and educational waste) was administered to a sample of (267) teachers chosen randomly. Results: The results showed that the level of the digital learning role in reducing educational loss from teachers’ perceptions was high, where the educational waste domain ranked first, at a high level, followed by skills loss at a high level as well, then cognitive loss at a medium level, while the emotional loss domain ranked lastly with medium level. The results showed a significant difference in the role of digital learning in reducing educational loss among students from teachers’ perceptions due to their academic qualifications in favor of (graduate studies and bachelor’s) categories, their experience in favor of (less than 5 years and 5-less than 10 years) categories, and their specializations in favor of (computer and information technology), while no differences appeared due to their gender. Conclusions: The study recommends the necessity of employing digital learning in the educational process, facilitating the process of transitioning to the digital learning system by preparing teachers and training them on digital learning skills and modern educational techniques, and focusing on developing the social and emotional capabilities of students, and working to reduce emotional loss, especially their loneliness and social isolation.